Job satisfaction and public service motivation. - Kaiser, Lutz C. (My University, 2014)
Based on a unique case study-dataset, the paper analyses job satisfaction and public service motivation in Germany. A special issue of the investigation is related to the evaluation of performance pay scales that were introduced some years ago to German public employees within the frame of fostering New Public Management. The findings display a general dominance of intrinsic motivators. Additionally, this kind of motivators plays an important role with regard to building up and keeping job satisfaction in the public sector. Further results display the transferability of competences, autonomy, regular appraisal interviews and productivity feedback as factors incorporating a positive significance in terms of job satisfaction.
Keywords: Verwaltung; Öffentlicher Dienst; Arbeitnehmer; Personalwesen; Öffentlicher Sektor; Arbeitszufriedenheit; Arbeitsmotivation